Synthesis of propenone-linked covalent organic frameworks via Claisen-Schmidt reaction for photocatalytic removal of uranium - Cheng-Peng Niu; Cheng-Rong Zhang; Xin Liu; Ru-Ping Liang; Jian-Ding Qiu (Nature Communications, 2023)
Abstract The type of reactions and the availability of monomers for the synthesis of sp 2 -c linked covalent organic frameworks (COFs) are considerably limited by the irreversibility of the C=C bond. Herein, inspired by the Claisen-Schmidt condensation reaction, two propenone-linked (C=C–C=O) COFs (named Py-DAB and PyN-DAB) are developed based on the base-catalyzed nucleophilic addition reaction of ketone-activated α-H with aromatic aldehydes. The introduction of propenone structure endows COFs with high crystallinity, excellent physicochemical stability, and intriguing optoelectronic properties. Benefitting from the rational design on the COFs skeleton, Py-DAB and PyN-DAB are applied to the extraction of radionuclide uranium. In particular, PyN-DAB shows excellent removal rates (>98%) in four uranium mine wastewater samples. We highlight that such a general strategy can provide a valuable avenue toward various functional porous crystalline materials.